Rounded corners columns strengthened with CFRP - doi: 10.4025/actascitechnol.v35i3.15124 - Santos, Leonyce Sousa de; Damasceno, Iana Ingrid Rocha; Ribeiro, Leila Cristina Nunes; Oliveira, Dênio Ramam Carvalho de (Acta Scientiarum. Technology, 2013)
Experimental results for twelve concrete columns with rectangular cross sections under axial compression are presented and discussed. Nine columns were strengthened with one layer of Carbon Fiber Reinforced Polymer (CFRP) at their ends. The study aimed to evaluate the performance of strengthened columns with several rounded corners radii. The results showed that the rounded corner columns presented a better performance and ultimate resistance but still with brittle failures. Â 